Harmonisation of Data Protection Regimes in the Southern African Development Community: Considering the influence of the SADC Model Law on Data Protection and the European Union on data protection laws in SADC - Ferreira, Christoff (Department of Commercial Law, 2022)
This minor-dissertation considers the issue of data protection coverage within the Southern African Development Community (SADC) and its importance to the Internet Telecommunications (ICT) sector in the various states of SADC but also its importance in providing protection to individuals in a region where internet penetration is increasing at a rapid pace. SADC introduced the SADC Model Law with the assistance of the Support for Harmonisation of the ICT Policies in Sub-Saharan Africa (HIPSSA Project). This is meant to provide a model in terms of which states in SADC could introduce or improve their own data protection regimes. Nevertheless, this instrument has not been successful in changing data protection practices within SADC, with only one state introducing a draft Bill on the basis of the Model Law. Nonetheless, despite the apparent failure of the Model Law, there will still be a degree of harmonisation between the various data protection laws in the sub-region due to the influence of the European Union (EU)'s Data Protection Directive. The approach taken is a comparative study which first considers the data protection laws of Mauritius and South Africa which have the two largest ICT sectors in SADC, the Zimbabwean draft Bill on Data Protection which was based on the SADC Model Law, and the Model Law itself. The purpose of this analysis is to determine whether a level of harmonisation has been achieved in SADC, despite the failure of the Model Law. The next step was a comparative study between the Model Law and the European Union's Data Protection Directive 95/46/EC and the General Data Protection Directive (GDPR) 2016/679. The purpose of this was to track the development of data protection law in the European Union due to the impact which these laws had on data protection globally and to show differences between data protection regimes in SADC and the European Union. The comparative study of laws in SADC illustrated that there is significant similarity between the laws considered, thereby proving that the Data Protection Directive played a more significant role in the harmonisation of data protection laws than the SADC Model Law. Nonetheless, the Model Law bared a significant resemblance to the other two existing data protection regimes. It also illustrated the weakness of the Model Law by demonstrating the lack of protection and shortcomings found in the Zimbabwean Bill based on the Model Law. The comparative study between the regimes in the EU and the Model Law illustrates disparities in the level of protection found in the Current European regime, the GDPR and in SADC. The GDPR is stricter than the Model Law and has extra-territorial application with the potential to apply in SADC. Further, the Model Law is based upon the Directive, and is, thus, outdated and weaker. The Model Law has, therefore, failed its stated goal of harmonising data protection laws in SADC yet there is still a degree of harmonisation due to the influence of the Data Protection Directive. The study showed the importance of having a strong data protection regime and also the shortcomings of existing regimes in SADC, when compared to the European Union.